An exploration of the solution of direct methanol fuel cell cost effectiveness - Wang, Tengyi; Luo, Zhiwei; Wang, Changsheng; Li, Yang; Chen, Xi; Tang, Yang; Wang, Xinsheng; Zhou, Zhiquan (Frontiers in Chemistry, 2024)
Work in this paper incorporated PCB technology into micro methanol fuel cells (µDMFCs), conjectured and verified the performance degradation factors of PCB current collectors µDMFCs by testing different designed configuration µDMFCs.Experiment results showed that all kinds of PCB coating can benefit from the porous stainless-steel plates covering to a great extent. At the end of 48h discharging, µDMFCs with porous stainless-steel plates between MEA and PCB coating can achieve higher performance than that direct contacting series. It can be inferred from various types of experimental data that attributed to the stainless-steel porous plate isolating, the impact of corrosion on the surface of the PCB electrode plate was reduced to a certain extent.The corrosion of the electrode plate was slowed down in the µDMFC discharging as a result of the passivation behavior on the iron surface and a decrease in corrosion current.Consequently, the attenuation of the PCB performance was delayed. Conclusions of this work explore a practical direction to enhance the cost effective of fuel cell, promoting the large-scale application of DMFC in the future.